Case report: A novel somatic SDHB variant in a patient with bladder paraganglioma - Nguyen, Thao; Ordulu, Zehra; Shrestha, Sunaina; Patel, Urja; Crispen, Paul L.; Brown, Lisa; Falzarano, Sara M.; Ghayee, Hans K.; Perdomo Rodriguez, Juan Pablo (Frontiers in Endocrinology, 2024)
Background Paragangliomas (PGL) are rare neuroendocrine tumors derived from the autonomic nervous system paraganglia. Urinary bladder paragangliomas (UBPGL) originate from the sympathetic neurons of the urinary bladder wall and represent 0.7% of all paragangliomas and <0.05% of all bladder tumors. PGL and UBPGL can be associated with SDHB, SDHD, NF1, and VHL gene variants, with the most common germline alterations found in SDHB and VHL. Case report We report a case of a 42-year-old woman who presented with menorrhagia/hematuria, uterine leiomyomas, as well as cardiac and bladder masses. The cardiac mass was favored to be a myxoma based on clinical findings, while the bladder mass was diagnosed as UBPGL. A novel SDHB mutation (c.642G>A, p Q214Q), detected in the UBPGL, was proven to be somatic. Although this variant was seemingly synonymous, it was predicted to have a loss of function due to the splice site effect, which was further supported by the immunohistochemical loss of SDHB. Conclusion This case highlights the challenges of diagnosing an extremely rare entity, bladder paraganglioma, with an emphasis on the multidisciplinary approach to navigate various clinical and imaging findings that may initially be misleading. In addition, a novel loss of function SDHB variant that could have been overlooked as a synonymous variant is herein reported, while also illustrating the importance of both germline and somatic mutation testing.